Implementasi Manajemen Pelayanan dalam Meningkatkan Mutu Pendidikan - Darussalam Malik; Nasrudin Harahap; Nurul Hidayati Murtafiah (Departement of Mathematics Education, 2023)
This study expects to analyze all the more profoundly the execution of administration the board in working on the nature of schooling. The examination utilized is distinct with a subjective methodology. expressed that the reason for engaging exploration is